Correlation of Railways and The Redjowinangun Market in Magelang 1903 - 1976 - Akbar Hidayah; Utami, Carolina Santi Muji (Universitas Negeri Semarang, 2024)
Trains are a means of mass transportation that may be familiar to the wider community. This mode is a means of transportation that is often chosen by many people to travel somewhere. The construction of rails which are part of the foundation on which train wheels stand in Indonesia has been carried out since the colonial era, pioneered by the Naamloze Venootschap Nederlandsch Indische Spoorweg Maatschappij (NV.NISM). The railway network was built based on the abundance of agricultural products since the implementation of the forced cultivation system, requiring transportation equipment that is strong and fast to carry heavy loads. The city of Magelang, as part of the Kedu Residency area, is the intersection of several cities which were planting areas for various colonial trade commodities. This research focuses on how the station in Magelang functions, which is connected to various cities, and how the lives of the people around the Magelang station will be after the network operates in the area. The aim of this research is to determine the sustainability of the station in Magelang and the impact it has on the lives of the surrounding community. The method used is the historical research method, including source collection (heuristics), source criticism (verification), interpretation (tafsir), and also historiography. The research results show that train stations, especially market stations in Magelang played an important role in the development of the local economy during the colonial period. Pasar Station is a symbol of long-standing socio-economic development. The emergence of economic activity around these stations is driven by several key factors, including increased mobility, goods transportation, and social interaction.